Revision of the Empis subgenus Enoplempis Bigot, east of the Rocky Mountains (Diptera: Empididae) - Sinclair, Bradley J.; Brooks, Scott E.; Cumming, Jeffrey M. (Zootaxa, 2013)
The Empis subgenus Enoplempis Bigot, east of the Rocky Mountains of North America is revised. A total of 19 species are recorded from this region including seven new species: E. (En.) amytis Walker, E. (En.) appalachicola Sinclair sp. nov., E. (En.) arthritica Melander, E. (En.) ctenonema Melander, E. (En.) enodis Melander, E. (En.) gladiator Melander, E. (En.) gulosa Coquillett, E. (En.) loripedis Coquillett, E. (En.) montywoodi Brooks sp. nov., E. (En.) nodipoplitea Steyskal, E. (En.) nuda Loew, E. (En.) pectinata Sinclair sp. nov., E. (En.) penicillata Brooks sp. nov., E. (En.) prodigiosa Cumming sp. nov., E. (En.) snoddyi Steyskal, E. (En.) stenoptera Loew, E. (En.) tridentata Coquillett, E. (En.) vockerothi Cumming sp. nov., E. (En.) volsella Sinclair sp. nov. The following new synonymies are designated: E. (En.) longipes Loew, E. (En.) longeoblita Steyskal, E. (En.) deterra Walley = E. (En.) amytis; E. (En.) cacuminifer Melander = E. (En.) gulosa. Lectotypes are designated for the following species: E. (En.) arthritica, E. (En.) cacuminifer, E. (En.) ctenonema, E. (En.) enodis, E. (En.) gladiator, E. (En.) loripedis, E. (En.) stenoptera and E. (En.) tridentata. A key to eastern species is presented and distributions illustrated. The form of nuptial gift presentation displayed within this group, including the use of balloons (with or without prey) and unwrapped prey are indicated for species when known.